Methods of forming foreign students’ information culture during pre-professional training in Ukrainian universities - Belikova, V.; Iakovenko, V. (Problems of Engineer-Pedagogical Education, 2018)
Relevance of the research comes from the growing influence of modern information technologies on an individual, including foreign students, and the need to develop new, adapted to the information society, technologies of foreign students training. The article deals with concretization the term "foreign students’ information culture" and its structure, proving in theory and developing the methods of forming foreign students’ information culture during preprofessional training in Ukrainian universities; the major components of the methods (goal, principles, contents, methods and materials) have been developed; major organizational and pedagogical conditions of educational process optimization on discipline "Fundamentals of informatics and computer science" are described. The article will be helpful for researchers, teachers and specialists of higher educational institutions dealing with the problems of training of specialists for foreign countries.